Psychiatrization, assertions of epistemic justice, and the question of agency - Russo, Jasna (Frontiers in Sociology, 2023)
Thus far, the concept of epistemic injustice in the context of psychiatry has been discussed more widely by clinical academics than by authors with personal experience of psychiatrization. It is from the latter perspective that I critique the practice of attributing testimonial injustice solely to the “stigma against mental illness,” and point to psychiatric diagnosing itself as a principal enabler and re-producer of this form of injustice. In relation to hermeneutical justice, I take a closer look at initiatives seeking to incorporate (collective) first-person knowledge into the epistemic systems that currently dominate mental-health service provision and research. Highlighting the incompatibility of psychiatric knowledge claims with first-person ways of knowing, I discuss some of the issues and challenges involved in achieving epistemic justice for psychiatrized people and advancing our collective knowledge base. Finally, I turn to the questions of identity and agency in these processes.